PENGARUH PEMBERIAN SQUARE STEPPING EXERCISE UNTUK MENINGKATKAN KESEIMBANGAN DINAMIS PADA LANSIA - Indah Pramita; Agus Donny Susanto (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2018)
Elderly is an advanced stage process that decreases the ability and function of the body. One of the declines that occur in the elderly is the musculoskeletal system in which it is very influential on balance. Square stepping exercise is one type of exercise that can be used in addition to increasing the strength of the musculoskeletal system, this exercise is also able to improve the visual ability. By increasing the ability of the musculoskeletal system, coupled with the visual ability is expected to improve balance in the elderly and reduce the risk of falling. The purpose of this research is to know the effect of Square stepping exercise on increasing the dynamic balance of elderly.This experimental study used a pre test and post test design. The sampling was done at Panti Wreda Sejahtera Denpasar. Elderly as many as 27 people who fit the criteria serve as a sample. The dynamic balance is evaluated by using the Time Up and Go test (TUG test) before and after the exercise. This study was conducted 3x a week for 4 weeks.Effect analysis test using Paired Sample test obtained p value = 0.001 with a balance increase of 27.92%. The conclusion of research that Giving Square Stepping Exercise can improve dynamic balance in elderly.Keywords: Elderly, Square Stepping Exercixe, Balance